Comparative toxicological-hygienic assessment, structural-morphological, physicochemical characteristics, and virucidal properties of new nanopowder materials TiO2 and TiO2@Ag - Yavorovsky, O.P.; Riabovol , V.M.; Zinchenko , T.O.; Zahornyi , M.M.; Ragulya , A.V.; Tyschenko , N.I.; Povnitsa, O.Yu.; Artiukh , L.O.; Zahorodnia , S.D.; Ostapiv , D.D. (Medicni Perspektivi, 2024)
In order to address safety concerns related to the acquisition and utilization of TiO2 and TiO2@Ag nanomaterials, as well as to investigate their disinfectant and biological effects, the structural-morphological, morphometry, toxicological, cytotoxic, and virucidal properties of these specified nanomaterials have been studied through experiments conducted on laboratory animals and in vitro. It has been demonstrated that the TiO2@Ag nanocomposite exhibited distinct physicochemical characteristics: it consisted of TiO2 nanoparticles ranging in size from 13 nm to 20 nm and Ag nanoparticles ranging from 35 nm to 40 nm with 4.0 wt% of silver localized on the surface of titanium dioxide. The purity of the modification of synthesized nano-TiO2 and nano-TiO2@Ag has been confirmed. Acute intraperitoneal administration of nanopowders revealed LD50 values of 4783.30 mg/kg for nano-TiO2 and 724.44 mg/kg for nano-TiO2@Ag. A slight accumulation was observed upon repeated (28-fold) intragastric administration of nano-TiO2. The cumulative dose administered, which equated to 15.9 multiples of the LD50 (76040 mg/kg), did not result in animal mortality but led to retardation in body weight gain. TiO2 and TiO2@Ag nanopowders do not irritate the skin, induce mild conjunctival irritation, and may exhibit a weak sensitizing effect. Nano-TiO2 and nano-TiO2@Ag powders accumulate in the tissues of internal organs and cause damage to the liver, kidneys, and lungs of laboratory animals upon intraperitoneal administration. The most characteristic morphological signs of the toxic effect of nano-TiO2 on liver tissue were observed at a level of 67.7% (cytoplasmic vacuolization in hepatocytes), while in the case of nano-TiO2@Ag initial necrotic changes were at a level of 70.0% (hepatocytes with pyknotic nuclei). Immunoassay analysis has demonstrated that TiO2@Ag and TiO2 nanomaterials at concentrations of 30 µg/ml can enhance the functional activity of peripheral blood mononuclear cells in vitro by increasing the production of cytokines IL-1, IL-6, TNF-α, and IL-4 in donors (p<0.05). This indicates the potential for chronic inflammation and allergic reactions among synthesis operators. In the study of the impact of nanomaterials on murine germ cells, it has been established that they affect the activity of mitochondrial enzymes and exert a damaging effect on mitochondrial membranes and overall cell integrity. Estimated approximate safe exposure levels in the workplace air are 0.3 mg/m3 for nano-TiO2 and 0.2 mg/m3 for nano-TiO2@Ag. Nano-TiO2@Ag and nano-TiO2 at a concentration of 100 µg/ml exhibit pronounced extracellular virucidal activity against human adenovirus serotype 2. The TiO2@Ag nanocomposite has a less damaging effect on Нер-2 cells compared to nano-TiO2.